Masyarakat Sipil dan Gerakan Politik: Studi Kasus Reformasi Bahrain - Abdullah, Abdullah (Department of International Relations, Brawijaya University, 2021)
In early 2011, countries in the Middle East and North Africa experienced a great mass movement that demanded their country leader to step down. Bahrain was one of the countries that experienced a mass movement, where the people of Bahrain demanded a government reformation that was considered authoritarian, repressive, and discriminative. The reformation that was wanted a change within the fields of politics, social, law and economy. This research aims to determine what factors causes the eruption of the mass movement in Bahrain on 2011. The writer used the concepts that the writer used to examine the problem using the concept mass movement by Eric Hoffer and the collective action by Charles Tilly and William Gamson. Based on the data there are and the theory the writer used, the factors that caused mass movement demanding reformation in Bahrain on 2011 are the disappointment from the people of Bahrain, the existence of organization and figure that's capable of mobilize the citizen, and also a special condition which is the mass movement that occurred in Egypt. Keywords: Mass Movement, Reformation, Bahrain